Electrotunable friction with ionic liquid lubricants - Bresme, F; Kornyshev, A; Perkin, S; Urbakh, M (Springer Nature, 2022)
Room-temperature ionic liquids and their mixtures with organic solvents as lubricants open a route to control lubricity at the nanoscale via electrical polarization of the sliding surfaces. Electronanotribology is an emerging field that has a potential to realize in situ control of friction—that is, turning the friction on and off on demand. However, fulfilling its promise needs more research. Here we provide an overview of this emerging research area, from its birth to the current state, reviewing the main achievements in non-equilibrium molecular dynamics simulations and experiments using atomic force microscopes and surface force apparatus. We also present a discussion of the challenges that need to be solved for future applications of electrotunable friction.